Bulk-synthesis and supercapacitive energy storage applications of nanoporous triazine-based graphdiyne. (15th October 2020) - Yue, Yong; Xu, Yongjie; Kong, Fanan; Li, Qingyin; Ren, Shijie
Abstract: Heteroatom doping and well-tuned porosity are regarded as two important pathways to enhance energy storage performance of porous carbon materials (PCMs). In this context, N-doped triazine-based graphdiyne (TGDY) and its hydrogen-containing counterpart HGDY were bulk-synthesized by Glaser coupling reaction from multi-acetylene monomers M1 and M2 respectively. TGDY exhibits a two-dimensional layer-by-layer structure and a high specific BET surface area of 785 m 2  g −1 . After heat-treatment at an optimized temperature of 800 °C, TGDY-800 shows a high specific capacitance of 250 F g −1 at 0.1 A g −1 and a remarkable capacitance retention of 97.6% at 1 A g −1 after 10, 000 cycles . These results are superior to HGDY-800 with similar structural skeleton and many other N-doped PCMs, indicating the synergetic effect of N-doping and high surface area. This work could effectively cast insight into designing of nanoporous carbon materials with good energy storage performance. Graphical abstract: Image 1